Pendampingan Lomba Cipta Puisi SMP Negeri 3 Tugu dalam Rangka Kegiatan Bulan Bahasa di STKIP PGRI Trenggalek Tahun 2024 - Fahrudin Fahrudin; Ayu Agustin (Manfaat : Jurnal Pengabdian Pada Masyarakat Indonesia, 2025)
Poetry creation as an activity that is very close to the participation of the soul in expressing all ideas. Of course, to express ideas and inspiration at least requires sufficient knowledge. Meanwhile, expressing the abilities that exist in students certainly needs to be known in advance what talents they have. Of course, in schools there is already talent development that has been developed, namely in the field of literacy. Therefore, to express the imagination and talents that exist in students, what can be done is that students are asked to create a poem.